Novye rossijskie issledovaniâ po političeskoj lingvistike - Čudinov, Anatolij P. (Stylistyka, 2021)
The present research investigates the main tendencies of modem Russian Political Linguistics based on the following oppositions: - research in the sphere of Political Linguistics - description of separate elements of the language of politics; - chronological framework of investigation: soviet, post soviet epoch; - levels of analyses: vocabulary, phonological system, word-building, morphology, syntax, text and discourse; - normative approach - descriptive approach which implies pure record and study of new phenomena without their estimation; - research of separate political genres, narratives and texts or study of some features common to the language of politics; - investigation of the idiostyle of some political leaders, political tren ds and parties or study of some regularities of the language of politics; - discourse research of communicative roles, rituals, strategies and tactics i. e. the language of politics under study; - use of the methods of psycholinguistics, cognitive science sociolinguistics, cultural linguistics, structuralism and others; - study of Russian political speech - comparative research of political discourse referred to different country epochs; - special investigations in the sphere of Political Linguistics - Political Linguistics materiał taken from works of other scientific fields.